GAMBARAN CITRA TUBUH PADA REMAJA KELAS IX DI SMPN 02 SRAGEN - Sila Alirga, Ananda Novi; Musslifah, Anniez Rachmawati; Purnomosidi, Faqih (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Teenagers will do anything to have an ideal body shape and in general they will follow the standards formed in society regarding the concept of appearance. Body image is an individual's view and assessment of their body appearance which forms a good or bad perception of a person. The purpose of this study was to determine the body image of grade IX adolescents at SMPN 02 Sragen. This study used a qualitative method with 5 informants, 2 male informants and 3 female informants. Data collection techniques were carried out by interview. The results of the study showed that the body image of the three informants was classified as less good, and two informants were classified as quite good. Even so, the informants made efforts to improve and care for themselves and tried to improve a positive body image.